Fatality as Portrayed in the Tragedies of Racine - Nelson, Neita Norma (My University, 1969)
A discussion of Fatality, its origin in the theatre; its effect on French tragedians up to Racine and its portrayal in Racinian tragedy.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures